Electromyography activities of upper and lower extremities in table tennis during forehand topspin and no spin stroke: A Case Study - Ozsu, I.; Simsek, D.; Ertan, H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this study was to compare upper and lower extremity muscles activations between the forehand topspin and no spin strokes. A right-handed male elite table tennis player performed 13 forehand topspin strokes and 13 forehand no spin strokes against a ball machine. Electromyography (EMG) activities from his 10 upper and lower extremity muscles were recorded during these strokes and analyzed using a wireless EMG device. According to descriptive statistics, there seemed to be high-level differences in muscular activities between forehand no spin and forehand topspin strokes.